2007
DOI: 10.1002/lt.21093
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for HCV cirrhosis: Improved survival in recent years and increased severity of recurrent disease in female recipients: Results of a long term retrospective study

Abstract: In recent years, a worsening outcome of hepatitis C virus (HCV)-positive recipients and a faster progression of recurrent disease to overt cirrhosis have been reported. Our aims were to 1) assess patient survival and development of severe recurrent disease (Ishak fibrosis score Ͼ 3) in different transplant years; and 2) model the effects of pre-and post-liver transplantation (LT) variables on the severity of recurrent disease. A multicenter retrospective analysis was conducted on 502 consecutive HCV-positive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 21 publications
6
93
2
3
Order By: Relevance
“…study (4 (18)(19)(20)(21)(22)(23)(24)(25)(26). AZA was associated with reduced severity of HCV recurrence in five studies (56%) (18,19,22,23,25), evaluated in a univariate analysis in one, multivariate in three, and with chi-square test in one, whereas in four studies (44%) (20,21,24,26) (5,19,23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), only two studies (12%) (31,33) found decreased severity of HCV recurrence, and in one (31) there was no multivariate analysis.…”
Section: Aza and Mmf In Liver Transplantationmentioning
confidence: 96%
See 1 more Smart Citation
“…study (4 (18)(19)(20)(21)(22)(23)(24)(25)(26). AZA was associated with reduced severity of HCV recurrence in five studies (56%) (18,19,22,23,25), evaluated in a univariate analysis in one, multivariate in three, and with chi-square test in one, whereas in four studies (44%) (20,21,24,26) (5,19,23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), only two studies (12%) (31,33) found decreased severity of HCV recurrence, and in one (31) there was no multivariate analysis.…”
Section: Aza and Mmf In Liver Transplantationmentioning
confidence: 96%
“…AZA was associated with reduced severity of HCV recurrence in five studies (56%) (18,19,22,23,25), evaluated in a univariate analysis in one, multivariate in three, and with chi-square test in one, whereas in four studies (44%) (20,21,24,26) (5,19,23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), only two studies (12%) (31,33) found decreased severity of HCV recurrence, and in one (31) there was no multivariate analysis. Nine studies (53%) (5,19,24,(26)(27)(28)(29)(30)32) documented similar severity of HCV recurrence, but six (35%) (23,(34)(35)(36)(37)(38) showed increased severity of HCV recurrence (Tables 2 and 3 …”
Section: Aza and Mmf In Liver Transplantationmentioning
confidence: 99%
“…In this study, donor age was a risk factor for mortality and graft failure only in HCV recipients, as it was not found to be significant factor in the non-HCV patients. The reason for the disproportionate risk with older donors in HCV patients is not known, but HCV recurrence is universal and is known to progress more rapidly in older grafts (23,26,27). Similar to non-HCV patients, HCV patients bare the risks of early graft failure related to advanced donor age, but in addition have longer term risks related to accelerated progression of recurrent HCV.…”
Section: Ghabril Et Almentioning
confidence: 99%
“…2 Recurrent HCV has an accelerated natural history with 20% to 54% of patients developing allograft cirrhosis within 5 years and reduced allograft and recipient survival. [3][4][5][6][7][8][9][10][11][12] Historically, recurrent HCV has been treated with peginterferon (PEG) and ribavirin (RBV) with rates of sustained virologic response (SVR) (undetectable HCV RNA at 6 months after end of treatment) of 28% to 45%. [13][14][15][16][17][18][19] Contributing to this relatively low SVR is a high prevalence of patients with HCV genotype 1 and the presence of cytopenias limiting the use of maximal dosing of PEG and RBV.…”
Section: Introductionmentioning
confidence: 99%